1976
DOI: 10.1007/bf00347413
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and metabolic bone disease in a zoological population

Abstract: Abstract. The radiologic survey technique used atthe National Zoological Park has disclosed many cases of nutritional and metabolic bone disease of various types. This communication discusses calcium deficiency states seen in lion cubs associated with a meat diet, the increased need for calcium noted in egg-laying lizards, problems found in New World monkeys, antelopes (due to selenium and/or vitamin E deficiency), hypervitaminosis D, and lead poisoning noted in young primates. In all of these diagnoses, the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In the present study the radiological findings included increased spinal column bone density (22.22% = 2/9), epiphysial moth-eaten osteolysis (11.11% = 1/9), solid periosteal reaction located the epiphysis and diaphysis (66.66% = 6/9), bone deformities located in epiphysis and in the diaphysis (88.88% = 8/9), epiphysial cortical tunneling (33.33% = 3/10) and inflammation of soft tissues (77,77% = 7/9), pathological fractures of the femur and urostyle (22.22% = 2/9) and spinal column deviations (100% = 9/9). All these alterations have been described in previous studies in other species with metabolic bone disease (Chang et al., 2016; Freedman et al., 1976; Patel et al., 2015).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the present study the radiological findings included increased spinal column bone density (22.22% = 2/9), epiphysial moth-eaten osteolysis (11.11% = 1/9), solid periosteal reaction located the epiphysis and diaphysis (66.66% = 6/9), bone deformities located in epiphysis and in the diaphysis (88.88% = 8/9), epiphysial cortical tunneling (33.33% = 3/10) and inflammation of soft tissues (77,77% = 7/9), pathological fractures of the femur and urostyle (22.22% = 2/9) and spinal column deviations (100% = 9/9). All these alterations have been described in previous studies in other species with metabolic bone disease (Chang et al., 2016; Freedman et al., 1976; Patel et al., 2015).…”
Section: Discussionsupporting
confidence: 73%
“…In humans, frequently described anomalies are subperiosteal bone resorption, periosteal reaction, intracortical, subchondral and endosteal resorption, brown tumors, pathologic fractures, diffuse increase in bone radiodensity and striped appearance of the spinal column (Chang et al., 2016; Patel et al., 2015). In reptiles there may be other additional anomalies such as a deformed spine and extensive periosteal bone formation that deforms the bone in an evident manner (Freedman et al., 1976). In this study, there were many alterations that were very similar, such as spinal column deformities, solid periosteal reaction in long bones, pathological fractures and epiphyseal cortical resorption or tunneling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9 New World primates seem to be particularly susceptible to metabolic bone diseases due to an inability to utilize vitamin D 2 , leading to a reliance on this conversion of pro-vitamin D 3 (7-dehydrocholesterol) to pre-vitamin D in the skin for vitamin D and calcium regulation. 10,11 Many New World primate species, including common marmosets (Callithrix jacchus), woolly monkeys (Lagothrix lagotricha), and Bolivian red howler monkeys (Alouatta seniculus), have documented cases of metabolic bone disease, but this case represents the first documented case, to our knowledge, of metabolic bone disease in a white-faced saki 10,[12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Melhus et al (1998) noted that human hypervitaminosis A can associate with lower bone mineral density and higher hip fracture risk. Ogden and Conlogue (1981) reported that bone changes of hypervitaminosis A may resemble radiographic lesions of vitamin D malabsorption (Breshau, 1957; Freedman et al, 1976), especially in the presence of excess liver intake. Taken together, these observations suggest that a relationship between hypervitaminosis A and inadequate calcium–phosphorus balance could be contextual, involving species, morphology, diet, and circumstance.…”
Section: Discussionmentioning
confidence: 99%